Alterações bioquímica e física da soja tratada com silicato de potássio visando o controle de Meloidogyne incognita - Mattei, Danielle (2018)
Root-knot nematodes (Meloidogyne spp.) are among the major phytopathogenic nematodes. Chemical nematicides present high toxicity, and alternative methods such as resistance induction are required. Silicon is considered a broad-spectrum inductor. The aim of this study was to evaluate the efficiency of doses of potassium silicate as an inducer for the control of Meloidogyne incognita in soybean, evaluating enzymatic activity, changes in the phenolic compounds and lignin contents and anatomical modifications. Soybean, cv. Syn. 1059, was induced, by spraying on shoot at phenological stage V1, with 0%, 0.25%, 0.5%, 1%, 2%, and 4% potassium silicate (Silifort®). Potassium chloride (KCl) at 0.04% K2O, acibenzolar-Smethyl (ASM) (Bion®, 200 mg L-1) and untreated and uninoculated plants were used as controls treatments. The inoculation with 3,000 eggs and eventual juveniles of M. incognita was carried out 10 or 8 days after treatments, depending on the assay. Evaluation of vegetative and nematological parameters was performed at 60 days. Root samples for enzymatic analysis were performed at 0, 4, 8, 12, 16 and 20 days after induction, and at the final, samples were collected for analysis of phenols, lignin and histology. Dunnett's test (5% probability of error) was performed. Linear, quadratic and cubic regression analyzes were performed for the doses. The 0.5% potassium silicate and ASM showed a reduction of more than 50% of the final population and reproduction factor of M. incognita. The final population, reproduction factor, nematodes per gram of roots and eggs per mass, showed lower values for dose around 0.8% of silicate. The enzymatic activity was not affected prior to inoculation. Polyphenoloxidase showed an increasing linear behavior (47% higher for 4% silicate), four days after induction. Phenylalanine ammonia-lyase presented at 2% silicate, at 12 days after induction, activity 72% higher than the control. In the same period, peroxidase showed a linear increase (55% higher to 4% silicate), and at 16 days, 2% showed activity 40% higher than dose 0. The silicate favored phenols accumulation and lignin decrease. The average of phenolic for silicate was lower than the control, but higher than KCl and ASM, and lignin, in general, did not differ from the control. Diameter of root and xylem vessels was not affected. Phloem diameter, its cells and xylem cells were lower for potassium silicate between 0.6% and 1.3% and higher for 3.3% to 4%. The wall thickness of the phloem and Casparian strip cells presented similar behavior, whereas xylem cells presented inverse behavior. Therefore, the influence of potassium silicate on enzymatic activity, phenol content, lignin and anatomical characteristics was confirmed in soybean challenged by M. incognita, indicating induction of resistance and priming, favoring root-knot nematode control.